Use of non-thermal plasma in lignocellulosic materials: A smart alternative - Pereira, Gabriela N.; Cesca, Karina; Vieira Cubas, Anelise Leal; de Oliveira, Débora (Trends in food science & technology, 2021)
Lignocellulosic materials are mainly composed of cellulose, hemicellulose, and lignin. They have been extensively used in recent years to obtain new value-added products, such as xylitol, vanillin, activated carbon, oligosaccharides, biofuels, among others. Biomass needs a pre-treatment to promote the breaking of the bonds that link the rigid macrostructures. The most common conventional pre-treatments are chemical. However, they cause significant damage to the environment since they either use toxic chemicals or produce waste, causing disposal problem. Non-thermal plasma is considered an environmentally friendly technique and is increasingly explored as a method of treatment and/or pre-treatment of lignocellulosic materials. In this review, we cover the main topics related to the use of non-thermal plasma technology (NTP) as a clean technology for the treatment of different lignocellulosic materials. We also address the main works on the subject and the main effects of this promising technology on different biomass. In addition to the main characterization techniques, we could find that it is possible to use this technique as an effective pre-treatment for future obtaining value-added products from different residues discarded in large quantities. Then, the main contribution of this review is to critically show the efficiency of this technology as an innovative and promising way to the treatment of different lignocellulosic residues. [Display omitted] •Potential application of non-thermal plasma (NTP) in lignocellulosic materials.•Use of NTP is considered non-toxic, viable and environmentally friendly.•Pre-treatment using NTP causes delignification due to the action of the ozone.•Prospects for the use of non-thermal plasma in lignocellulosic biomass.